2006
DOI: 10.2975/30.2006.141.144
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Program-Wide Awareness about Recovery in a Large Mental Health and Addictions Program.

Abstract: St. Joseph's Healthcare Hamilton conceptualized a multi-step plan for implementing a recovery oriented service delivery approach within their Mental Health and Addictions Program. This brief report discusses the first phase of this plan which included building awareness of recovery utilizing Anthony's (2000) system standards to develop a needs assessment for managers and senior team members. The survey had three purposes: to increase managers' awareness about recovery; to allow managers to express concerns tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Related literature suggests that many mental health providers still hold negative views about the potential for people with SMI to move beyond the limits of mental illness (Chinman, Klood, O'Connel, & Davidson, 2002;. McVanel, Younger, Doyle, and Kirkpatrick (2006) indicated that a significant barrier to recovery was providers" resistance to change and negative attitudes towards recovery. With the recognition that service providers may not have attitudes, knowledge or skills, attention has been focused on identifying the provider competencies required for effectively delivering recovery-oriented services.…”
Section: General Introductionmentioning
confidence: 99%
“…Related literature suggests that many mental health providers still hold negative views about the potential for people with SMI to move beyond the limits of mental illness (Chinman, Klood, O'Connel, & Davidson, 2002;. McVanel, Younger, Doyle, and Kirkpatrick (2006) indicated that a significant barrier to recovery was providers" resistance to change and negative attitudes towards recovery. With the recognition that service providers may not have attitudes, knowledge or skills, attention has been focused on identifying the provider competencies required for effectively delivering recovery-oriented services.…”
Section: General Introductionmentioning
confidence: 99%
“…While the idea of moving towards recovery-oriented reform is generally accepted by system planners and administrators, the actual implementation of recovery principles into organizational structures and practices continues to be of concern (McVanel-Viney, Younger, Doyle, & Kirkpatrick, 2006). Implementation obstacles encompass conceptual, philosophical, attitudinal, and practical matters.…”
Section: Challenges Of Implementing Recovery-oriented Carementioning
confidence: 99%
“…Moreover, 90% of Japanese psychiatric hospitals are private, and hospitals with many long‐term inpatients have low medical fees from the national government and are often financially constrained (MoHLW, 2022). One approach to supporting practice change has been through training (Gilburt et al., 2013; McKenna, Furness, Dhital, Park, & Connally, 2014), but managers have identified a lack of training and financial resources for recovery as barriers (McVanel‐Viney et al., 2006). Further, because of a lack of funds, no time has been spent to support new interventions such as recovery, which is reflected in healthcare workers' lack of enthusiasm (Whitley et al., 2009).…”
Section: Discussionmentioning
confidence: 99%